TRANSFORMASI PERPUSTAKAN KHUSUS BERBASIS INKLUSI SOSIAL : INOVASI PERPUSTAKAAN PERTANIAN - Sutarsyah Sutarsyah; Eka Kusmayadi; Widaryono Widaryono; Herwan Junaedi (VISI PUSTAKA: Buletin Jaringan Informasi Antar Perpustakaan, 2022)
In line with the development of the main tasks of the organization, special libraries undergo changes and development of services by transforming through the expansion of the variety of users. And with the library program based on social inclusion, all elements of society get equal treatment and get equal opportunities, to improve their quality of life and welfare. This paper aims to provide information on the innovation of the Center for Library and Agricultural Technology Dissemination (PUSTAKA) in the Social Inclusion-Based Special Library (PKBIS) program, in synergy with the Agricultural Extension Center (BPP), extension workers have a strategic role as the spearhead in agricultural development because they are directly related to farmers. . Following are the activities of PKBIS PUSTAKA; 1. Coordination and socialization at BPP and in the village, 2. Arrangement of the Cibungbulang BPP Library and Benteng Village Library, by providing collections, bookcases, appointing library managers, arranging books, etc. 3. Improve the skills and competencies of BPP Cibungbulang extension workers and farmers through technical guidance on video production, sweet potato grading, sweet potato cultivation, library management, etc., and Literacy, information delivery to farmers based on LIBRARY publications related to yam cultivation and other crops, story telling competitions 4. Increasing the added value of farmer's farming through workshops and technical guidance on farming, 5. Training on controlling sweet potato pests. This study was conducted using a descriptive method, namely by collecting data systematically by taking data sources from the report on the activities of the PKBIS Cibungbulang semester 1. The data collection was carried out in May s.d. August 2022. The results of the study showed that extension workers and farmers responded positively to PKBIS PUSTAKA activities by applying the results of technical guidance, the posluhdes team in the implementation of the extension field to farmers brought books and brochures, and showing videos as part of literacy in increasing farmers' knowledge. It can be concluded that the PKBIS PUSTAKA program can increase the knowledge of extension workers and farmers.